Topical Delivery of Eberconazole Nitrate Loaded Microemulsion: Formulation, Design and Evaluation (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
The objective of the present research work was to develop microemulsion for the transdermal delivery of eberconazole nitrate (EBZ). Initially oil, surfactant and co-surfactant were selected based on their solubility and emulsification study respectively. Pseudo ternary phase diagram was constructed to optimize the surfactant-co surfactant (Smix) ratio. Eberconazole nitrate (EBZ) loaded microemulsion was optimized using central composite design (CCD) with amount of Capmul MCM (X1), tween 80 (X2) and Transcutol (X3) as independent variables along with cumulative amount of drug release (Q24) (Y1), flux (Jss) (Y2) and lag time (tL) (Y3) as dependent variables. Drug release study of all the design batches showed successfully increased permeation of drug which might be due to compositional characteristics of ME. The globule size of the optimized batch of EBZ loaded ME (153.6nm) confirms the micrometer size of the formulation. Zeta potential and polydispersity index (PDI) of optimized batch was found to be -30.5 mV and 0.253 respectively which proved stability and uniform distribution of dispersed systems respectively. The optimized batch of MEs has the pH value of 6.96 ±0.21 which indicate there is no chance of skin irritation. Further Morphological and structural examination of the optimized batch of EBZ loaded ME was done by transmission electron microscope (TEM) and images illustrated the spherical micelles with size range of 100 – 200 nm which evidently may support the high absorption and results into enhancement of drug permeation which may increase the therapeutic effect, decrease the dose frequency and improving the patience compliance for topical drug delivery.